Asthma and mental health among youth: etiology, current knowledge and future directions. (August 2012) - Goodwin, Renee D; Bandiera, Frank C; Steinberg, Dara; Ortega, Alexander N; Feldman, Jonathan M
Asthma and mental health problems, such as depression, anxiety and behavior disorders, are common among youth and are significant sources of morbidity. There is a consistent association between asthma and anxiety/depression and a less consistent association between asthma and behavior disorders. Possible biological and psychological mechanisms may include inflammatory processes as well as the stress of having to live with a life-threatening condition. Future studies are warranted with longitudinal designs to establish temporality as well as measures of potential confounds. Biological and psychological measures would complement the longitudinal design to further establish causality. In addition, more information on the degree to which asthma and mental health have reciprocal influences on each other over time – and the mechanisms of these relationships – are needed in order to develop more effective intervention strategies to improve asthma control and mental health among those with both.